Waste bank-socio-economic empowerment nexus in Indonesia: The stance of Maqasid al-Shariʻah - Miftahorrozi Miftahorrozi; Shabeer Khan; Muhammad Ishaq Bhatti (Journal of Risk and Financial Management, 2022)
With the rapid increase of waste throughout the country, the government of Indonesia has enacted regulations targeting waste reduction using religious sentiment. This is employed in Malang City's "Waste Bank of Malang" (WBM). This study aims to analyze the impact of waste banks on socio-economic progress, and to assess their efficacy in accomplishing this objective from the Maqasid al-Shariʻah perspective. The research employs a descriptive qualitative approach and uses both primary and secondary data sources. This study found that the operation of WBM contributes considerably to the community's economic and social well-being. Likewise, the WBM has successfully managed waste by reducing, reusing, and recycling it as it is collected from customers. The customers receive financial incentives from the waste bank in return for providing recycled waste to a specialized firm under a profit-sharing (PLS) contract. As per the findings of the study, the rationale of the waste bank aligns with the Maqasid al-Shariʻah and the Islamic finance contract of PLS arrangements.
Keywords: 650; Maqasid al-Shariʻ ah; socio-economic empowerment; waste; Waste Bank of Malang